Experimental Study of The Influence Use of Beeswax Against The Mechanical and Thermal Properties of Concrete - Fazri Amir; Banta Cut; Rayan Rayan; Baidatul Khoir; Nasruddin Nasruddin; Muhammad Amin (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2020)
The economy of the whole world developed so quickly, encourage increased consumption of energy gradually. Energy consumption in the building sector has also increased with the demands of society in thermal comfort in the room. With the hot weather, the influence of the temperature in the room will rise. Some things that need to be reviewed in the manufacture of concrete in the place are the price is relatively low, easy to obtain, has high compressive strength, and has resistant to any environmental conditions. However, some problems still need to be resolved in the development of the Phase Change Material (PCM) composite that has a stable form. The proposed PCM has a thermal comfort temperature (16-26 ℃). The main purpose of this research was to investigate the influence of addition beeswax as a water-resistant mixture on the mechanical and thermal properties of concrete. In this research, the cement used was ordinary Portland Cement and replaced some of its Weight with paraffin wax in the mixture. The results of the research with the use of 10, 20 and 30% beeswax in a mixture of a concrete show that the increase in the content of Beeswax resulted in a decrease in the compressive strength of 22% and an increase in heat absorption by the concrete between without PCM with the Concrete-PCM is obtained by 10%.